Sistem Informasi Pengelolaan Surat Masuk dan Surat Keluar untuk Mendukung Kinerja Administrasi di UPT BLK Situbondo - Suudi Hidayat; A. Hamdani; Rizaldy Baguz Faiz Kusuma (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The management of incoming and outgoing mail at the Situbondo Technical Implementation Unit (UPT BLK) plays a crucial role in supporting the effectiveness of administrative activities. Currently, the process of recording letters is carried out manually using an agenda book, which is considered inefficient, makes searching for archives difficult, and takes a long time. These problems encourage the implementation of an information system that can facilitate faster, more structured, and more accurate processing of letter data. This study proposes the development of a computer-based information system using the waterfall method in the Software Development Life Cycle (SDLC). The data collection process is carried out through direct observation and interviews with administrative staff, so that system requirements can be clearly identified. The results of this study are an information system design with a simple, user-friendly, and easy-to-operate interface, so that employees can quickly understand the flow of use. The system developed allows the process of recording, archiving, and tracking letters to be more organized, practical, and efficient compared to previous manual methods. In addition, this system is also able to reduce the potential for human error in recording and accelerate the presentation of information when needed for administrative purposes and decision-making. Other advantages offered are easy data access and the availability of reliable, accurate, and timely information. With this system, administrative performance at the Situbondo Technical Implementation Unit (UPT BLK) is expected to significantly improve, both in terms of time efficiency, service speed, and orderliness in managing documents.